Deciphering the microbial succession and color formation mechanism of “green-covering and red-heart” Guanyin Tuqu - Zhu, Liping; Chen, Liang; Lin, Bin; Xu, Yin; Dong, Weiwei; Lv, Yijun; Tang, Jie; Zhang, Gang; Zhang, Lei; Yang, Shengzhi; Yang, Qiang; Chen, Shenxi (Frontiers in Microbiology, 2024)
“Green-covering and red-heart” Guanyin Tuqu (GRTQ), as a type of special fermentation starter, is characterized by the “green-covering” formed on the surface of Guanyin Tuqu (SQ) and the “red-heart” in the center of Guanyin Tuqu (CQ). However, the mechanisms that promote temporal succession in the GRTQ microbial ecology and the formation of “green-covering and red-heart” characteristics remain unclear. Herein, we correlated the temporal profiles of microbial community succession with the main environmental variables (temperature, moisture, and acidity) and spatial position (center and surface) in GRTQ throughout fermentation. According to the results of high-throughput sequencing and culture-dependent methods, the microbial communities in the CQ and SQ demonstrated functional complementarity. For instance, the bacterial richness index of the CQ was greater than that of SQ, and the fungal richness index of the SQ was greater than that of CQ at the later stage of fermentation. Furthermore, Saccharomycopsis, Saccharomyces, Aspergillus, Monascus, Lactobacillus, Bacillus, Rhodanobacter, and Chitinophaga were identified as the dominant microorganisms in the center, while the surface was represented by Saccharomycopsis, Aspergillus, Monascus, Lactobacillus, Acetobacter, and Weissella. By revealing the physiological characteristics of core microorganisms at different spatial positions of GRTQ, such as Aspergillus clavatus and Monascus purpureus, as well as their interactions with environmental factors, we elucidated the color formation mechanism behind the phenomenon of “green” outside and “red” inside. This study provides fundamental information support for optimizing the production process of GRTQ.